Development of contrast-induced acute kidney injury after elective contrast media exposure in patients with type 2 diabetes mellitus: effect of albuminuria. - Jun-qing Yang; Peng Ran; Ji-yan Chen; Yi-ting He; Li-wen Li; Ning Tan; Guang Li; Shuo Sun; Yong Liu; Jia-xin Zhan; Jian-yi Zheng; Ying-ling Zhou (PLoS ONE, 2014)
The influence of albuminuria and urinary pH on the development of contrast-induced acute kidney disease (CI-AKI) in patients with type 2 diabetes mellitus (T2DM) after elective coronary angiography (CAG) or percutaneous coronary intervention (PCI) is unknown.CI-AKI was defined as an increase in serum creatinine >26.4 µmol/L or ≥50% of baseline value within 48 hours after contrast media exposure. Demographics, traditional risk factors, clinical outcomes and CI-AKI incidence were compared between groups. Univariate analysis and multivariate logistic regression were performed to assess risk factors of CI-AKI.We observed 597 patients with T2DM after CAG or PCI. Patients were divided into 3 groups based on early morning urinary albumin: negative group (urine dipstick negative, n = 483), trace group (urine dipstick trace, n = 60), and positive group (urine dipstick ≥1+, n = 54). CI-AKI occurred in 33 (5.5%) patients, including 19 (3.9%) in the negativealbuminuria group, 4 (6.7%) in the trace group, and 10 (18.5%) in the positive group (p< 0.001), respectively. After adjusting for potential confounding risk factors, positive albuminuria (OR = 3.8, 95% CI: 1.5 to 9.2, p = 0.004) and urinary pH<6 (OR = 2.4, 95% CI: 1.1 to 5.1, p = 0.020) remained significantly associated with CI-AKI.Preprocedural albuminuria and urinary pH <6 are independent risk factors of CI-AKI in patients with T2DM undergoing elective cardiac catheterization, and may be used to identify patients at high risk of post-procedural CI-AKI.